Dynamically Regulated Ag Nanowire Arrays for Detecting Molecular Information of Substrate‐Induced Stretched Cell Growth. Issue 43 (15th September 2016) - Zhang, Zhen; Fu, Yu; Yu, Wei; Qin, Xiaoyun; Xue, Zhenjie; Liu, Yan; Luo, Dan; Yan, Cong; Sun, Xiaohua; Wang, Tie
Abstract : The modified coffee‐ring effect is used to self‐assemble highly uniform, long‐range‐ordered Ag nanowire arrays. As the oriented Ag nanowire arrays provide excellent membranes for surface‐enhanced Raman scattering, the molecular mechanism of cell adhesion and growth is systematically studied and well understood. This work has important significance for life science research.